The Teacher Control Book as a Reflective Instrument in the Development of Teacher Professionalism - Widiawaty, Andi; Akbar, Muhammad; Nurhayati, Nurhayati (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study aims to describe the implementation of the teacher control book as a strategy for developing teacher professionalism at SMPIT Al Qalam Kendari. Teacher professionalism plays a vital role in improving educational quality, and the teacher control book serves as a reflective instrument to foster discipline, responsibility, and self-evaluation among teachers. This research employed a qualitative approach with a descriptive design. The participants consisted of five teachers, one principal, and one quality management staff member selected through purposive sampling. Data were collected through participatory observation, in-depth interviews, and document analysis. The data were analyzed inductively using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the teacher control book contributed positively to enhancing teacher professionalism in several key aspects: improving discipline and accountability, strengthening pedagogical competence through continuous reflection, increasing the effectiveness of data-based academic supervision, and promoting more systematic teaching administration. Furthermore, the teacher control book fostered a reflective and collaborative culture among teachers, creating a productive and accountable professional environment. Overall, the implementation of the teacher control book at SMPIT Al Qalam Kendari has proven to be an effective strategy for developing teachers who are disciplined, adaptive, and committed to continuous professional growth and educational quality improvement.